Bicuculline blocks nicotinic acetylcholine response in isolated intermediate lobe cells of the pig. - Zhang, Z. W. (1991)
1. The effect of bicuculline on nicotinic acetylcholine (ACh) responses in isolated intermediate lobe (IL) cells of the pig was investigated by use of patch-clamp techniques. Bicuculline was found to reduce ACh-evoked whole-cell currents (IACh) in all cells tested (n = 40). 2. The blocking effect of bicuculline on IACh was dose-dependent, the concentration producing half-maximal blockade being 43.8 microM. 3. The blockade of IACh by bicuculline was not voltage-dependent at membrane potentials above -60 mV, but a slight voltage-dependence was observed at holding potentials (HP) of -80 and -100 mV. 4. The inhibitory effect of bicuculline on IACh was partially competitive at a HP of -60 mV. 5. Neither SR 95531, a pyridazinyl gamma-aminobutyric acid derivative, nor t-butylbicyclophosphorothionate (TBPS) blocked IACh in IL cells. 6. It is concluded that bicuculline interacts directly with the ACh receptor-ionophore complex on porcine IL cells.